2016
DOI: 10.1007/s12161-016-0673-5
|View full text |Cite
|
Sign up to set email alerts
|

Method Validation and Determination of Polycyclic Aromatic Hydrocarbons in Vegetable Oils by HPLC-FLD

Abstract: The aim of this work was to determine the level of contamination of different groups of vegetable oils available on the Polish market with polycyclic aromatic hydrocarbons, i.e. benzo(a)pyrene and sum of benzo(a)pyrene, benz(a)anthracene, benzo(b)fluoranthene and chrysene, the content of which in foodstuffs is limited by Commission Regulation (EU) 2015/1125 of 10 July 2015. The research materials were refined rapeseed oils, sunflower oils, olive pomace oil, rapeseed oils with olive oil and unrefined soybean an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 17 publications
0
15
1
1
Order By: Relevance
“…The presence of PAH in these oils indicates a lower efficiency of refining processes, higher temperature used during the rapeseed conditioning or risk of exogenous pollutions. The concentrations of PAH in the studied rapeseed oils were lower in comparison with the results of B[a]P (0–1.92 μg kg −1 ), Chry (0–2.40 μg kg −1 ), B[a]A (0–1.30 μg kg −1 ), and B[b]F (0–1.35 μg kg −1 ), as well as Σ4PAH (0–6.0 μg kg −1 ) reported by Zachara et al () and Larsson et al () for refined rapeseed oils.…”
Section: Resultscontrasting
confidence: 64%
“…The presence of PAH in these oils indicates a lower efficiency of refining processes, higher temperature used during the rapeseed conditioning or risk of exogenous pollutions. The concentrations of PAH in the studied rapeseed oils were lower in comparison with the results of B[a]P (0–1.92 μg kg −1 ), Chry (0–2.40 μg kg −1 ), B[a]A (0–1.30 μg kg −1 ), and B[b]F (0–1.35 μg kg −1 ), as well as Σ4PAH (0–6.0 μg kg −1 ) reported by Zachara et al () and Larsson et al () for refined rapeseed oils.…”
Section: Resultscontrasting
confidence: 64%
“…Due to the lack of appropriate reference materials representing the composition of tea, the results of PAH determination in black dried tea by HPLC-FLD method proceeded by extraction and purification procedure by QuEChERS technique were compared to the respective results of PAH determination by the method with use of glass chromatographic column packed with alumina [ 26 ]. Taking into account the uncertainty estimated for each of the methods, it was found that there were no statistically significant differences between the obtained results ( Figure 2 ); therefore, the QuEChERS method can be recommended for determination of PAHs in tea due to considerably shorter analysis time and less chemical reagent consumption.…”
Section: Resultsmentioning
confidence: 99%
“…In the initial stage of the research, a comparison of two methods of extraction and purification of the PAHs was made [ 25 ]: the method involved use of a glass column filled with aluminum oxide [ 26 ] and the QuEChERS procedure. For this purpose, a sample of black tea was used.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Then, the extract is cleaned up using a solid phase extraction column (silica, alumina, florisil, etc.). Available scientific reports have described the analysis via different techniques of extraction, purification and detection (Zachara et al 2017a; IARC Working Group on the Evaluation of Carcinogenic Risks to Humans 2010; Conchione et al 2015;Zachara et al 2017b;Rey-Salgueiro et al 2009;Kumari et al 2013;Liu et al 2016). Zachara et al (2017b) adopted a method including the process of saponification, extraction and clean-up using a self-made column packed with aluminum oxide for the determination of PAHs in vegetable oils.…”
Section: Introductionmentioning
confidence: 99%